Boosting neighbourhood identification to benefit wellbeing: Evidence from diverse community samples. (June 2022) - Cruwys, Tegan; Fong, Polly; Evans, Olivia; Batterham, Philip; Calear, Alison L.
Abstract: Emerging research has suggested the importance of neighbourhood identification for supporting community wellbeing, especially in disadvantaged areas. However, these relationships have not been tested across diverse neighbourhoods, nor in experimental studies that might establish causal links. To address this, we recruited a diverse community sample of over 3700 participants across two studies. Study 1 was a survey ( N  = 1617 from 772 distinct neighbourhoods) and found that neighbourhood identification is a mechanism through which neighbourhood socioeconomic status affects wellbeing. Study 2 was an experiment ( N  = 2109 from 909 distinct neighbourhoods) that found that neighbourhood identification could be enhanced through a subtle framing manipulation, which in turn predicted wellbeing, loneliness, and social cohesion. These effects were not moderated by neighbourhood socioeconomic status. Findings are discussed with a focus on implications for designing effective interventions to support community wellbeing. Highlights: Neighbourhood disadvantage predicts poorer wellbeing. Reduced neighbourhood identification partially explained this relationship. Two studies were conducted with >3700 people from >900 neighbourhoods. Experimental evidence found that neighbourhood identification could be increased. Neighbourhood identification also predicted social cohesion and reduced loneliness.